Indirect spetopotometric Assay of Paracetamol in Pharamaceutical Preparations Via Oxidative Coupling Reaction with 1-Naphthol and Metaperiodate - Intisar K.Mohamad; Elham Salih; Thabit Al-Ghabsha (College of Education for Pure Sciences, 2005)
Development of indirect Spectrophotometric method for the determination of paracetamol in pure form as well as dosage form is described. The method is based on the acid hydrolysis of paracetamol to p-aminophenol followed by oxidative coupling reaction with 1-naphthol in the presence of sodium metaperiodate in alkaline medium to form a blue indophenol dye which absorbs at 600nm. Beer's law is obeyed in the concentrations range of 1.2-24 j.ig/ml with a molar absorptivity of 9.65 x 103 1. mol'1. cm"1., accuracy (average recovery) is 100.91% and precision (RSD) is less than 2.5%. Common excipients used as additives in pharmaceuticals do not interfere in the proposed method. The method is successfully employed for the determination of paracetamol in